A high-resolution and high-efficiency x-ray spectrometer based on a multi-cone crystal. (1st June 2023) - Shang, W L; Wei, M X; Yang, G H; Sun, A; Zhang, Z Y; Du, H B; Wang, F; Yang, J M; Li, M; Shi, J
Abstract: A curved x-ray spectrometer based on a multi-cone crystal has been developed and demonstrated to improve the spectra resolution and intensity efficiency measurements by our experiments and simulations. Here 6000 conical rings with a single-ring of 10 μm to free the stress on the lattice planes was successfully realized in the multi-cone crystal, which provides a much larger solid collection angle and higher resolution than the usually-used planer crystal in the general x-ray spectrometer. Thus, the experimental results show that its spectrum resolution can reach ∼3.5 eV (full-width half maximum) with the corresponding E / Δ E of 1420 (∼4976 eV). The intensity at the focus spot can be 110 times higher compared to that measured by a planer crystal spectrometer. Meanwhile, these results have also been confirmed by our numerical studies with our new developed x-ray arbitrary-surface-crystal diffraction software, X-chase. Attentional development on the x-ray spectrometer is of specific importance in the high energy density physics, inertial confinement fusion, and Astrophysics experiments.